2017
DOI: 10.2196/jmir.7997
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Interventions to Promote HIV Testing, Linkage, Adherence, and Retention: Systematic Review and Meta-Analysis

Abstract: BackgroundSocial media is increasingly used to deliver HIV interventions for key populations worldwide. However, little is known about the specific uses and effects of social media on human immunodeficiency virus (HIV) interventions.ObjectiveThis systematic review examines the effectiveness of social media interventions to promote HIV testing, linkage, adherence, and retention among key populations.MethodsWe used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist and Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
121
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 172 publications
(131 citation statements)
references
References 51 publications
9
121
0
1
Order By: Relevance
“…Influencers could also serve as leaders in network-based, social media interventions to allow health messages to reach more MSM [37]. We found among influencers a higher rate of social media engagement about HIV testing and a higher likelihood of having used social media for HIV testing than other MSM, suggesting influencers may be readily incorporated into social media HIV interventions [37]. Influencers additionally contribute by being well positioned in social networks to spread behavior change.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Influencers could also serve as leaders in network-based, social media interventions to allow health messages to reach more MSM [37]. We found among influencers a higher rate of social media engagement about HIV testing and a higher likelihood of having used social media for HIV testing than other MSM, suggesting influencers may be readily incorporated into social media HIV interventions [37]. Influencers additionally contribute by being well positioned in social networks to spread behavior change.…”
Section: Discussionmentioning
confidence: 77%
“…For example, influencers could serve as steering committee members of crowdsourcing contests that aim to promote testing [30,46]. Influencers could also serve as leaders in network-based, social media interventions to allow health messages to reach more MSM [37]. We found among influencers a higher rate of social media engagement about HIV testing and a higher likelihood of having used social media for HIV testing than other MSM, suggesting influencers may be readily incorporated into social media HIV interventions [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in high-, middle-, and low-income countries have demonstrated that social media experiences can promote STD testing [23,24]. A study in the United Kingdom found that offering internet-accessed STD testing increased test uptake and decreased the time to get tested, however, it did not reduce time to treatment [25].…”
Section: Discussionmentioning
confidence: 99%
“…Examples of novel interventions include the use of vending machines to offer HIV tests,11 home specimen collection for STI testing12 and using GSN app pop-up messages to refer users to a website to order home-delivered HIV self-test kits 5. Ultimately, GSN apps are just one method of reaching MSM who may be at high risk for HIV and STIs, but multiple methods, including other social media platforms13 and traditional outreach, are needed to curb the HIV and STI epidemics among MSM.…”
mentioning
confidence: 99%